EPIDEMICAL IMPORTANCE OF LUNG TUBERCULOMA, THE EFFICIENCY OF THEIR SURGICAL AND NON- SURGICAL TREATMENT BASED ON DATA FROM THE REPUBLIC OF TATARSTAN - R. Sh. Valiev; N. R. Valiev; I. Ya. Iksanov; M. S. Filatova (Туберкулез и болезни лёгких)
It was identified, that the proportion of lung tuberculoma is insignificant among TB cases with bacterial excretion and destruction of lung tissue, therefore their epidemical risk is low.The analysis of relapses after surgical and non-surgical treatment of patients with lung tuberculoma was performed at 4-7 years after the completion of treatment which demonstrated that the frequency of relapses after both modes of treatment has no valid difference. However, the course of relapses in operated patients is more severe than in non-operated patients and the cost of treatment for surgical modes is significantly higher. It is necessary to revise the indications for surgical treatment of this form of tuberculosis.